Difficulties encountered by elementary school pupils in interpreting graphs - Autor, Anita Clacio- 1951- (1977)
This paper attempted to identify, determine and analyze the difficulties encountered by Grade V pupils in interpreting graphs in elementary mathematics. The subjects of this study were one hundred twenty five (125) Grade V pupils from two randomly selected classes in Nabua Pilot Central School and Lagonoy Central School in the division of Camarines Sur during the school year 1977-1978. The schools selected are using the UP-SEC Elementary School Mathematics text. A diagnostic test constructed by the researcher and checked and validated by some selected mathematics teachers and the research paper adviser was first tried out on some randomly selected Grade Six pupils of Balara Elementary School in Quezon City and the University of Nueva Caceres in Naga City. Implications such as the reading skills closely tied up with the ability to solve problems and inadequate knowledge in interpreting graphs arise from the findings of the study.